2015
DOI: 10.1007/s10029-015-1353-x
|View full text |Cite
|
Sign up to set email alerts
|

Slow femoral venous flow and venous thromboembolism following inguinal hernioplasty in patients without or with low molecular weight heparin prophylaxis

Abstract: In the immediate postoperative period, inguinal hernioplasty with mesh induces a temporarily slow venous flow in the ipsilateral CFV. However, this does not lead to an increase in the incidence of VTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A few previous studies have directly evaluated slow venous flow, and others have indirectly assessed patients at risk with presumed or confirmed venous stasis. Direct evaluations include work by Lozano et al, who assessed 218 patients in the immediate postoperative period after ipsilateral inguinal hernioplasty with mesh placement. That study demonstrated short‐term slowing of deep venous flow without an increased incidence of venous thromboembolism and near normalization of flow 7 days thereafter .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A few previous studies have directly evaluated slow venous flow, and others have indirectly assessed patients at risk with presumed or confirmed venous stasis. Direct evaluations include work by Lozano et al, who assessed 218 patients in the immediate postoperative period after ipsilateral inguinal hernioplasty with mesh placement. That study demonstrated short‐term slowing of deep venous flow without an increased incidence of venous thromboembolism and near normalization of flow 7 days thereafter .…”
mentioning
confidence: 99%
“…Direct evaluations include work by Lozano et al, who assessed 218 patients in the immediate postoperative period after ipsilateral inguinal hernioplasty with mesh placement. That study demonstrated short‐term slowing of deep venous flow without an increased incidence of venous thromboembolism and near normalization of flow 7 days thereafter . An even shorter duration of slow venous flow was shown during intraperitoneal insufflation for laparoscopy, without evidence of an increased rate of DVT .…”
mentioning
confidence: 99%
“…By measuring the minimum blood velocity in the common femoral vein on the surgical side, flow velocity in the ipsilateral femoral vein was lower than that of the contralateral femoral vein (20.9 cm/s vs. 24.0 cm/s; p < 0.001) 9 . The diameter of the ipsilateral common femoral vein was larger than that on the contralateral side (p < 0.001), although this was found only with left inguinal hernia operation 9 . But in other publications such an observation has not been confirmed yet.…”
Section: Discussionmentioning
confidence: 92%
“…In a prospective study published in 2015, in the immediate postoperative period, inguinal hernioplasty with mesh induces a temporarily slow venous flow in the ipsilateral CFV. However, this does not lead to an increase in the incidence of VTE 9 . In addition, to avoid postoperative hematoma or seroma, some doctors use postoperative inguinal compression, which may also lead to VTE clinically.…”
mentioning
confidence: 97%
“…There are a small number of studies of vein flow velocity and its role in postoperative dvt. Some studies were conducted in laparoscopic, gastric bypass and inguinal hernioplasty patients, where vein flow velocity was followed up postoperatively as a predictor factor of postoperative dvt, without assessing preoperative vein flow velocity [10][11][12] . during thA, the lower limb is placed in many different positions, of which in some positions such as hyperflexion the veins can be compressed and blood flow velocity decreased, leading to vein stasis, possible thrombus formation, and consequent dvt and vte [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%